The 1st International Electronic Conference on Forests—Forests for a Better Future: Sustainability, Innovation, Inter 2020
DOI: 10.3390/iecf2020-08032
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Morphology of the Leaf Epidermis in Four Species of Meliaceae L. Family

Abstract: Meliaceae is a family of woody species that are very useful for timber and ethnomedicine in Nigeria. However, there is scarce information on their taxonomic description, which is important in realizing their full potentials. Existing floristic studies on members of Meliaceae have revealed overlap in key morphological characters like number of lateral nerves, shape, size and number of leaflets. Aside the floral and fruit characters, the use of leaf epidermal characters has proven to be gene-dependent and as suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Principal component analysis (PCA) can be used to determine the relative contribution of each character to the total variation and to identify the most informative character to represent the existing variability using the corresponding factor loadings within the species (Arriel et al 2007;Akinyele et al 2020). PCA has also been used by various authors to evaluate the systematic importance of various attributes (Paul and Chowdhury 2021).…”
Section: Leaf Anatomical Characters Variationmentioning
confidence: 99%
“…Principal component analysis (PCA) can be used to determine the relative contribution of each character to the total variation and to identify the most informative character to represent the existing variability using the corresponding factor loadings within the species (Arriel et al 2007;Akinyele et al 2020). PCA has also been used by various authors to evaluate the systematic importance of various attributes (Paul and Chowdhury 2021).…”
Section: Leaf Anatomical Characters Variationmentioning
confidence: 99%
“…Polygonal epidermis cells were examined on both leaf sides of Plantago albicans , adaxial surface of Plantago weldenii , and on lower surface of Mentha longifolia . Hence, it was concluded that variances existed among the same species belonging to the same family members (Akinyele et al, 2020).…”
Section: Discussionmentioning
confidence: 99%